PENGEMBANGAN MEDIA PEMBELAJARAN IPA-FISIKA SMARTPHONE BERBASIS ANDROID SEBAGAI PENGUAT KARAKTER SAINS SISWA - Siti Fatimah; Yusuf Mufti (Kaunia: Integration and Interconnection Islam and Science, 2014)
Smartphone is one type of telecommunication device that is widely used by the public, both children and adults. One of popular smartphone is based on Android platform. It have many advantages which can help people in developing creativity and not limited by time. In the world of education it is seen still need to be optimized to achieve the objectives of national education systems, especially as science instructional media. This research is a development research 4D’s model (Define, Design, Develop, Desseminate) wich limited by the “Develop” step. This product have been valued by 1 instructional media expert, 1 science material expert, and 1 teacher of the SMP/MTs. Then the product have been tried out to the students is MTs Nurul Ummah at VII grade by using sample 6 students for limited test and 30 students have been involved in the field research. The result of this research have produced a science instructional media based on Android Smartphone with criteria Very Good.